IMPROVING STUDENTS’ SPEAKING COMPETENCE THROUGH SIMULATION TECHNIQUE: A Classroom Action Research in the Third Semester Students of Management Department of Economics Faculty, Kadiri University - Vitasmoro, Pamadya (English Education:Journal of English Teaching and Research, 2017)
This research aims at observing the implementation of simulation teaching technique to the teaching of English speaking at Management Program of Economics Faculty of Kadiri University and its effect upon the students’ learning. The research was conducted for the third semester students. In this research, the problems refers to their speaking competence is still low. Related to the above problem, the writer thinks that simulation teaching technique is the most appropriate one that can be used to increase their motivation to study English especially English speaking. The research methodology included setting and time of the research, the subject of the research, the procedure of the research, technique of collecting the data, and technique of analyzing the data. The writer divided the action into two cycles and carried out in four steps namely action plan, action implementation, observation, and reflection. The cycles were determined at the time of implementation in which after looking the result of the first cycle, then followed by the next cycles to see the consistency of the significant data. The result of the implementation showed that the use of simulation improved and enhanced the students’ English speaking competence. Based on the above result, it could be concluded that the use of simulation teaching technique really improved the students’ achievement in learning English especially in English speaking. Related to the research findings above, the writer wanted to recognize the most appropriate teaching technique. Secondly, create the most appropriate approach to make the students not to be shy, nervous, and afraid to make mistakes, or even feel inferior to communicate with others in English. The last, create an interesting and enjoyable atmosphere during the class activity in order to make the students easier and more bravery to express their own English orally.